-3+1=4*3-5-3*3

Simple and best practice solution for -3+1=4*3-5-3*3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+1=4*3-5-3*3 equation:


Simplifying
-3 + 1 = 4 * 3 + -5 + -3 * 3

Combine like terms: -3 + 1 = -2
-2 = 4 * 3 + -5 + -3 * 3

Multiply 4 * 3
-2 = 12 + -5 + -3 * 3

Multiply -3 * 3
-2 = 12 + -5 + -9

Combine like terms: 12 + -5 = 7
-2 = 7 + -9

Combine like terms: 7 + -9 = -2
-2 = -2

Add '2' to each side of the equation.
-2 + 2 = -2 + 2

Combine like terms: -2 + 2 = 0
0 = -2 + 2

Combine like terms: -2 + 2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -14x+7y=-21 | | y-16=.25 | | -9x+30=-12 | | 8y^2+6y-35=0 | | -x-5=-2 | | X+(2X)+(X+2ft)=70 | | 10m+5=5 | | -x-2=-5 | | 9-2x=6x-15 | | 3(x-0.5x)-2x=132 | | .33=h+.4 | | 165u-4= | | 68-2x=79-3x | | t-23.5=39.7 | | 36=(8)-(14x) | | 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 | | 2(3x+1)-x=3 | | B-(2)=-11 | | 14-4y=y+x |

Equations solver categories